Endoplasmic Reticulum Stress in Spinal Cord Contributes to the Development of Morphine Tolerance - Liu, Daiqiang; Zhou, Yaqun; Peng, Yawen; Su, Peng; Li, Zheng; Xu, Qiaoqiao; Tu, Ye; Tian, Xuebi; Yang, Hui; Wu, Zhen; Mei, Wei; Gao, Feng (Frontiers in Molecular Neuroscience, 2018)
Morphine tolerance remains an intractable problem, which hinders its prolonged use in clinical practice. Endoplasmic reticulum (ER) stress has been proved to play a fundamental role in the pathogenesis of Alzheimer's disease, diabetes, atherosclerosis, cancer, etc. In this study, we provide the first direct evidence that ER stress may be a significant driver of morphine tolerance. Binding immunoglobulin protein (BiP), the ER stress marker, was significantly upregulated in neurons in spinal dorsal horn in rats being treated with morphine for 7 days. Additionally, chronic morphine treatment resulted in the activation of three arms of unfolded protein response (UPR): inositol-requiring enzyme 1/ X-box binding protein 1 (IRE1/XBP1), protein kinase RNA-like ER kinase/eukaryotic initiation factor 2 subunit alpha (PERK/eIF2α), and activating transcription factor 6 (ATF6). More importantly, inhibiting either one of the three cascades could attenuate the development of morphine tolerance. Taken together, our results suggest that ER stress in spinal cord might contribute to the development of morphine tolerance. These findings implicate a potential clinical strategy for preventing morphine tolerance and may contribute to expanding the morphine usage in clinic.